Factors resulting in conversion of laparoscopic cholecystectomy to open cholecystectomy-institution based study - Awan, Naseer Ahmad; Hamid, Firdous; Mir, Irfan Nazir; Ahmad, Mir Mujtaba; Shah, Ajaz Ahmad; Asimi, Athar; Nafee, Alfar Ah; Wani, Hilal Ahmad (International Surgery Journal, 2017)
Background: Laparoscopic surgery has revolutionized the way it is performed for an increasing number of patients. In this study, we determined the various reasons for conversion of laparoscopic cholecystectomy in our setup. Methods: This was a descriptive study, conducted at Government Medical College Srinagar, Frommay 2015 to June 2017. The study included 450patients with symptomatic cholelithiasis, who underwent laparoscopic cholecystectomy. All patients were operated by experienced laparoscopic surgeons with experience of more than 300 Laparoscopic cholecystectomies. Cases that required conversion from laparoscopic to open surgery were analyzed and the factors possible for such conversion were studied. Results: The mean age of patients was 45.6 years and male to female ratio 1:3.8. The mean operating time was 49 minutes and average hospital stay was 2 days. Out of 450 patients, 26(5.8%) required open conversion. Factors responsible for open conversion were dense adhesions in 12(2.7%), obscure anatomy at clot’s triangle in 6, (1.3%), significant intra-operative bleeding 5 (1.1), CBD injury 1(0.2%), visceral injury 1 (0.2%), and instrument failure in 1(0.2%) conversions. Conclusions: Open conversion rate of laparoscopic cholecystectomy in this study was 5.8%. The commonest cause of conversion was dense adhesions around the gall-bladder. Preventable factors like instrument failure or power breakdown can be addressed by a reliable back up.